CONCEPTUAL AND METHODOLOGICAL ASPECTS OF FORMATION OF STRATEGY FOR ENSURING ECONOMIC SECURITY - RUZHYTSKYI, IHOR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The components of the strategy of economic security in Ukraine are proposed, the key purpose of which is to determine the model of actions and means of the system of economic security, development of the main directions, forms, methods and tools for achieving strategic goals; it is argued that this strategy should include five sections (1. Preamble. 2. General provisions. 3. Purpose, main directions and tasks. 4. Mechanisms. 5. Indicators) the implementation of which involves the joint efforts of government and society on levels of the state, regions and local self-government. To implement the strategy it is necessary to perform a set of tasks: to determine the basic parameters of environmentally safe condition; identify the priorities of economic policy in relation to the objectives of economic security; substantiate the ways and means of achieving the objectives of economic security; to form a set of measures to ensure the achievement of certain goals and objectives; identify the necessary resources for the implementation of certain tasks, as well as conditions and factors that ensure the greatest efficiency of their use; to ensure effective organization of monitoring the implementation of strategic planning documents in ensuring economic security. The mechanism for implementing the strategy involves combining the efforts of government and society at the state, regional and local governments to coordinate the strategy with existing comprehensive target programs and monitor its implementation based on targets. Information and information-analytical support for the implementation of this strategy is provided by the coordinating role of the relevant Ministry through the involvement of information resources of interested public authorities and public research institutions. Implementation of the economic security strategy should be ensured through the adoption of new laws and other regulations, amendments to legal acts in the field of agriculture and environmental protection, as well as the development of the State Program for Economic Security in Ukraine for 2022- 2024